The evolution of the Chinese housing market and its impact on base metal prices - Mark Kruger; Kun Mo; Benjamin Sawatzky (Bank of Canada, 2016)
The Chinese housing market has grown rapidly following its liberalization in the 1990s, generating significant economic activity and demand for base metals. In this paper, we discuss the evolution of the Chinese housing market and quantify its importance for the overall Chinese economy and its linkages to base metal prices. We estimate that the housing boom was responsible for roughly a quarter of the 85 per cent increase in base metal prices from 2002 to 2010. Since 2014, however, a substantial inventory overhang has led to a steep correction in the housing market, which in turn has contributed up to a third of the 25 per cent decline in base metal prices. While the drag on metal prices should ease as the Chinese housing market stabilizes, the level of support from this sector will likely remain minimal compared with the experience of the past decade.
Keywords: Q31; R31; 330; International topics